2002
DOI: 10.1023/a:1014576505223
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Autogenic training (AT) is a self-relaxation procedure by which a psychophysiological determined relaxation response is elicited. A meta-analysis was performed to evaluate the clinical effectiveness of AT. Seventy-three controlled outcome studies were found (published 1952-99). Sixty studies (35 randomized controlled trials [RCT]) qualified for inclusion in the meta-analysis. Medium-to-large effect sizes (ES) occurred for pre-post comparisons of disease-specific AT-effects, with the RCTs showing larger ES. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(68 citation statements)
references
References 58 publications
3
62
0
3
Order By: Relevance
“…Therefore, a corresponding taxonomy including clear definitions for each strategy was developed for this app analysis. In addition to the emotion-focused stress management strategies that have been investigated by Coulon et al [24] (namely breathing exercises [25-27], progressive muscle relaxation [26,28], meditation or mindfulness [29-31], and visualization or guided imagery [26,32]), the following evidence-based strategies were identified during a thorough literature review: autogenic training [33], biofeedback [26], emotional freedom technique or acupressure [26,34], euthymic methods [35], hypnosis or self-hypnosis [36], (self-)massage [37], and physical stress relief techniques such as yoga [38] or tai chi [39]. As stress sensations can also be influenced by some types of music [40,41], sounds of nature [42], nutrition [43], and sport [44], these aspects were also included (see Table 1 for an overview and definitions).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a corresponding taxonomy including clear definitions for each strategy was developed for this app analysis. In addition to the emotion-focused stress management strategies that have been investigated by Coulon et al [24] (namely breathing exercises [25-27], progressive muscle relaxation [26,28], meditation or mindfulness [29-31], and visualization or guided imagery [26,32]), the following evidence-based strategies were identified during a thorough literature review: autogenic training [33], biofeedback [26], emotional freedom technique or acupressure [26,34], euthymic methods [35], hypnosis or self-hypnosis [36], (self-)massage [37], and physical stress relief techniques such as yoga [38] or tai chi [39]. As stress sensations can also be influenced by some types of music [40,41], sounds of nature [42], nutrition [43], and sport [44], these aspects were also included (see Table 1 for an overview and definitions).…”
Section: Introductionmentioning
confidence: 99%
“…After pre-testing, 40% of the selected women achieved CRF-level above the age-normalized values based on the equation of Fitzgerald et al (1997), VO 2 max = 43.82 ¡ 0.35 (age in years), revealing greater than desired physical condition, and were therefore excluded from the analysis. We used autogenic training (AT) to control the physical activity level of the non-exercising group and because changes in strength or cardiorespiratory Wtness were not expected (Brochu et al 2002;Stetter and Kupper 2002). The Wnal number of female participants analyzed were ST ht = 7, ST ss = 8, ET i = 7, ET c = 9, and AT = 11 to test our hypotheses.…”
Section: Subjectsmentioning
confidence: 99%
“…A previous study reported that AT is clinically effective for not only improving mood and cognitive performance but for treating tension headache, migraine, mild-to-moderate essential hypertension, and coronary heart disease [23]. …”
Section: Introductionmentioning
confidence: 99%